2019
DOI: 10.1093/pubmed/fdz033
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of extreme heat events on hospital admissions to the Royal Hobart Hospital

Abstract: Background Extreme heat (EH) events are increasing in frequency and duration and cause more deaths in Australia than any other extreme weather event. Consequently, EH events lead to an increase in the number of patient presentations to hospitals. Methods Climatic observations for Hobart’s region and Royal Hobart Hospital (RHH) emergency department admissions data were collected retrospectively for the study period of 2003–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…The number of days with more frequent coercive interventions increased with a rise in temperature (positive but poor), and increased with a drop in air pressure (negative correlation). In various regions of the world, extreme heat events lead to an increase in the number of patient presentations to hospitals due to mental illness [51][52][53], but in our study, where patients were kept in closed hospital wards, the effect seemed to be much smaller, statistically bordering significance. Moreover, the short series of data (only two summer seasons) does not allow for a more precise analysis of the relationship between the number of hot days and the aggressive behavior of patients.…”
Section: Meteorological Conditions On Days With High Number Of Physical Coercion Eventscontrasting
confidence: 76%
“…The number of days with more frequent coercive interventions increased with a rise in temperature (positive but poor), and increased with a drop in air pressure (negative correlation). In various regions of the world, extreme heat events lead to an increase in the number of patient presentations to hospitals due to mental illness [51][52][53], but in our study, where patients were kept in closed hospital wards, the effect seemed to be much smaller, statistically bordering significance. Moreover, the short series of data (only two summer seasons) does not allow for a more precise analysis of the relationship between the number of hot days and the aggressive behavior of patients.…”
Section: Meteorological Conditions On Days With High Number Of Physical Coercion Eventscontrasting
confidence: 76%
“…In recent years, multiple studies have demonstrated the effects of heatwaves on excess ambulance demand, hospital admissions and mortality in several sites across Australia 18,19 . This indicator tracks change in a measure of heatwave intensity — the excess heat factor — as it applies to human health 20,21 .…”
Section: Section 1: Climate Change Impacts Exposures and Vulnerabilitymentioning
confidence: 99%
“…Time series generalised linear models of the quasi-Poisson distribution of ED presentations19 20 and gamma distribution for ED costs21 were applied to model the relationships with temperature. The effects of temperature exposure can be related to the current day’s temperature or to exposure on previous days 22.…”
Section: Methodsmentioning
confidence: 99%